ANALYSIS OF APPLICATION OF ENTERPRISE ARCHITECTURE FOR MODERNISATION OF AIR TRAFFIC MANAGEMENT SYSTEMS - Kredentsar, Svetlana; Yastrub, Maksym (Proceedings of National Aviation University (archive), 2019)
Purpose: Due to growing demand for air transportation and a shortage of current capacities of air traffic management systems to accommodate future air traffic, there is a need to transform current air traffic management systems. Any change in a complex system like an air traffic management system might have an impact on various stakeholders, the performance of the system and its safety. Thus, there is a need for means to assess and predict the impact of a change as well as plan its introduction in the most efficient way. Methods: An enterprise architecture provides means to have a holistic view on complex systems like air traffic management system allowing to assess the impact of the changes and help to deploy them. Results: It can be seen that the enterprise architecture is used by various agencies, organizations and enterprises across the world to better manage and plan their activities. The same methodology could be applied to air traffic management systems to enable their transformation to accommodate the increasing demand for air transportation. From the performed research, it can be seen that the enterprise architecture has been used by major research programs in the United States and Europe to plan the transformation of their air traffic management systems and ensure smooth and timely deployment of the results of the research programs. Discussion: While allowing to get a holistic overview of the state of the enterprise, it might be a challenge to introduce an enterprise architecture at the enterprise. A wide set of experts is required to describe the enterprise from different perspectives (business, operational, technological, etc.) which makes the process quite time-consuming. However, there are a number of enterprise architecture frameworks and architecture development methods to facilitate more smooth and fast deployment of the enterprise architecture.